Exploitative Leadership and Emotional Exhaustion among Retail Employees: Gender Differences and The Moderating Role of Gender - Norlaili, Nadia; Wijanarkor, Adrian A (Jurnal Manajemen, 2026)
This research is motivated by increasing attention to the impact of negative leadership styles on employee psychological well-being, particularly in the context of exploitative work leadership. The main problem in this research is how the influence of exploitative leadership towards emotional Employee exhaustion in the work environment. The purpose of this study is to analyze and empirically test the influence of exploitative leadership towards emotional exhaustion. This study used a quantitative approach with a survey method. The research sample consisted of 95 respondents selected using purposive sampling techniques according to predetermined criteria. Data were collected through questionnaires and analyzed using simple linear regression analysis with the help of a statistical program. The results of the study show that exploitative leadership has a positive and significant influence on emotional exhaustion with a regression coefficient of 0.291 and a significance value of 0.001 (<0.05). The t-value of 3.414 indicates that the research hypothesis is accepted. In addition, the results of the coefficient of determination test show an R- square value of 0.111, which indicates exploitative leadership contributes 11.1% to emotional exhaustion, while 88.9% is influenced by other variables outside the research model. These findings indicate that the higher the level of exploitative leadership behavior, the higher the level of employee emotional exhaustion. Thus, this study provides an empirical contribution to the literature on destructive leadership and burnout and emphasizes the importance of ethical and supportive leadership practices in organizations.